Calcium pectinate and hyaluronic acid modified lactoferrin nanoparticles loaded rhein with dual-targeting for ulcerative colitis treatment. (1st July 2021) - Luo, Ruifeng; Lin, Meisi; Fu, Chaomei; Zhang, Jinming; Chen, Qiyan; Zhang, Chen; Shi, Jinfeng; Pu, Xiulan; Dong, Linlin; Xu, Haiting; Ye, Naijing; Sun, Jiayi; et al.
Highlights: A promising food-grade and ecofriendly oral nano-delivery system was developed. Dual-targeting of NPs corresponded to dual-bioresponsibilities of RH. First to attempt for LF as a targeting nanomaterial in UC treatment. CP increases the stability of NPs and control drug release upon colonic lesion. RH has good effects in UC treatment both from anti-inflammatory and mucous repair. Abstract: Herein, dual-bioresponsive of Rhein (RH) in promoting colonic mucous damage repair and controlling inflammatory reactions were combined by the dual-targeting (intestinal epithelial cells and macrophages) oral nano delivery strategy for effective therapy of ulcerative colitis (UC). Briefly, two carbohydrates, calcium pectinate (CP) and hyaluronic acid (HA) were used to modify lactoferrin (LF) nanoparticles (NPs) to encapsulate RH (CP/HA/RH-NPs). CP layer make CP/HA/RH-NPs more stable and protect against the destructive effects of the gastrointestinal environment and then release HA/RH-NPs to colon lesion site. Cellular uptake evaluation confirmed that NPs could specifically target and enhance the uptake rate via LF and HA ligands. in vivo experiments revealed that CP/HA/RH-NPs significantly alleviated inflammation by inhibiting the TLR4/MyD88/NF-κB signaling pathway and accelerated colonic healing. Importantly, with the help of CP, this study was the first to attempt for LF as a targeting nanomaterial in UC treatment and offers a promising food-based nanodrug in anti-UC.